Impaired cough reflex in patients with recurrent pneumonia. Issue 2 (1st February 2003) - Niimi, A; Matsumoto, H; Ueda, T; Takemura, M; Suzuki, K; Tanaka, E; Chin, K; Mishima, M; Amitani, R
Abstract : Background: A substantial proportion of patients with recurrent pneumonia do not have an apparent underlying condition, but they may have unknown defects in host defence mechanisms such as cough reflex. Methods: Capsaicin cough sensitivity was measured in seven patients with recurrent pneumonia but no underlying condition. Recurrent pneumonia was defined as at least two episodes of pneumonia in 1 year, or three or more episodes at any time. After remission of pneumonia, 10 doubling concentrations of capsaicin (1.22–625 μM) were inhaled until five or more coughs were induced (cough threshold). Mucociliary clearance was assessed on the basis of nasal ciliary beat frequency and nasal clearance time. Twenty one age and sex matched healthy subjects were studied as controls. Results: Each patient had 2–6 episodes of pneumonia. Most episodes developed in dependent lung segments, suggesting the involvement of silent aspiration. Log transformed cough threshold was significantly higher in patients than in controls (mean 2.37 M (95% CI 1.84 to 2.90) v 1.29 μM (95% CI 1.11 to 1.47); p<0.0001). The effect of pneumonia per se on cough reflex seemed unlikely since the cough threshold showed little change when re-examined after 3 months. The patients and controls did not differ with respect to the indices of mucociliary clearance. Conclusions: Impaired cough reflex may be involved in the pathogenesis of recurrent pneumonia.